Power of perception: on South African paradigms, pneumatology and theology - Marais, N (Nederduitse Gereformeerde Teologiese Tydskrif, 2010)
If paradigms power perception, how then is spirit and Spirit to be understood within the multicultural, multi-ethical, and multiple layers of society in a South African context? Paradigms are constantly evolving and growing in multiplicity and complexity, especially when interacting with one another. In this article an explorative study is undertaken into some prominent macro-level influences that shape paradigms. Attention is paid to culture, heritage and history, socio-politics, economic realities, and ideology, with a focus on spirituality that “impacts on the totality of life” (Kourie, 2000:13). This paper aims to explore the relationship of perceptions and paradigms that shape an understanding of spirit and Spirit within a South African context. Lastly, it (perhaps daringly so!) refers to the current church unification process of the Dutch Reformed Church and Uniting Reformed Church in South Africa in the course of the reflection on paradigms, pneumatology and theology.